2020
DOI: 10.1108/ijbm-05-2020-0288
|View full text |Cite
|
Sign up to set email alerts
|

Not all elderly are the same: fostering trust through mobile banking service experience

Abstract: PurposeThis study seeks to examine the impact of mobile service experience on trust of elderly consumers in their financial institution and assess whether age (55–64 years vs 65+ years) exerts a moderating influence.Design/methodology/approachA self-administered questionnaire was completed online by 390 panelists (aged 55 years or more) who use their mobile devices to conduct banking activities. A multigroup analysis was conducted to assess the moderating role of age.FindingsResults confirm the presence of lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 109 publications
0
32
3
3
Order By: Relevance
“…Accordingly, in the case of the Baby Boomer generation, the Baby Boomer birth period varies from country to country (Sudbury-Riley et al, 2015 ). Moreover, although some studies propose the search for heterogeneity within generational cohorts (Rajaobelina et al, 2021 ), other studies have indicated that the differences are not associated with demographic variables such as age but rather psychographic variables such as cognitive age (Arenas-Gaitán et al, 2020 ). In this context, we follow the recent study of Ramírez-Correa et al ( 2019a ) that operationalized the Chilean generations in a digital setting.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in the case of the Baby Boomer generation, the Baby Boomer birth period varies from country to country (Sudbury-Riley et al, 2015 ). Moreover, although some studies propose the search for heterogeneity within generational cohorts (Rajaobelina et al, 2021 ), other studies have indicated that the differences are not associated with demographic variables such as age but rather psychographic variables such as cognitive age (Arenas-Gaitán et al, 2020 ). In this context, we follow the recent study of Ramírez-Correa et al ( 2019a ) that operationalized the Chilean generations in a digital setting.…”
Section: Introductionmentioning
confidence: 99%
“…Samsudeen et al [14] in "the setting of mobile learning in Sri Lanka found age to have a moderating influence on effort expectancy and social influence". "Concerning age, security and comfortability are found to be sophisticated in older respondents as compared to younger ones" [10]. "Aged people tend to have higher technology worry and are less technologically inventive compared to young customers.…”
Section: The Moderation Effect Of Agementioning
confidence: 98%
“…The aged ones tend to be relatively left behind in terms of technology used for conducting businesses as they are skeptical about the technology where they trust more direct businesses. Rajaobelina et al [10] found "age to be a robust predictor of trust in new product ownership in the customer electronics group". "Age is determined to have a moderating influence on technology use and insights" [11].…”
Section: The Moderation Effect Of Agementioning
confidence: 99%
“…Aspectos como el diseño o la simplificación en la estructura de navegación serían de gran ayuda a la hora de evitar los frenos que estos usuarios declaran. En este sentido emergen también barreras relacionadas con el tratamiento de los datos personales pretel-jimenez, m., m., & abad-alcalá, l. Factores clave que determinan la relación y el uso... y bancarios, como los requerimientos de información que estipulan las compañías a la hora de realizar devoluciones, a pesar de que estas medidas buscan aumentar su confianza (Rajaobelina et al, 2020). De hecho, un diseño accesible y una estrategia de contenido inclusivo permitirían a las empresas de comercio electrónico ampliar su negocio entre este segmento poblacional (Karahasanovic et al, 2009).…”
Section: Conclusiones Y Discusiónunclassified